Superluminal propagation in artificial electromagnetic structures : doctoral thesis - Bonić, Ivan (I. Bonić ; Fakultet elektrotehnike i računarstva, 2020)
This thesis is devoted to electromagnetic metamaterials (MTM), which are artificial structures with special electromagnetic properties that are not normally found in naturally occurring materials. Besides their unusual physical properties, some MTM-based electromagnetic structures can support superluminal propagation (propagation with velocities faster than the speed of light in vacuum c). Main goal is engineering of active superluminal structures and characterization of their electromagnetic properties. Superluminal propagation phenomena found in some passive MTMs are compared to the novel concept of active broadband non-Foster-based superluminal MTMs that support broadband phase or group velocity. A causal model of non-Foster-based epsilon-near-zero (ENZ) active MTM is developed and tested analytically and numerically. These active ENZ MTMs are ultra-wideband and support superluminal group velocity and superluminal phase velocity. In the end, the proposed theoretical approach is simulated and non-Foster negative capacitors in RF regime are designed, built and optimized. Furthermore, the proposed transmission-line-based non-Foster ENZ 1D MTM was built and tested in RF 2 MHz to over 40 MHz band. The experiments were conducted in both frequency and time domain, confirming the stable operation and the permittivity that is lower than the permittivity of vacuum (the ENZ behavior). The extractions further show that this medium has ultra-wideband EM characteristics that cannot be achieved with any existing passive MTMs. The post processing of extracted parameters revealed simultaneous superluminal phase velocity and superluminal group velocity within the bandwidth of more than four octaves. The superluminal behavior of the prototype was also demonstrated by measurements in time domain with the sinusoidal and Gaussian burst excitation signals. These measurements also revealed the superluminal behavior of pulses that are qualitatively very similar to previous “fast light” time-domain superluminal experiments in physics. The achieved theoretical and experimental results enable causal modeling of future stable 1D and 2D volumetric active non-Foster based MTMs that support ultra-wideband superluminal pulse propagation. Keywords: RF, ENZ, active metamaterial, superluminal propagation, superluminal group velocity, causality, non-Foster, Lorentz dispersion, active medium